Core localized alpha-channeling via low frequency Alfvén mode generation in reversed shear scenarios. (1st December 2022) - Wei, Shizhao; Wang, Tao; Chen, Liu; Zonca, Fulvio; Qiu, Zhiyong
Abstract: A novel channel for fuel ions heating in tokamak core plasma is proposed and analyzed using nonlinear gyrokinetic theory. The channel is achieved via spontaneous decay of reversed shear Alfvén eigenmode (RSAE) into low frequency Alfvén modes, which then heat fuel ions via collisionless ion Landau damping. The conditions for RSAE spontaneous decay are investigated, and the saturation level and the consequent fuel ion heating rate are also derived. The channel is expected to be crucial for future reactors operating under reversed shear configurations, where fusion alpha particles are generated in the tokamak core with the magnetic shear being, typically, reversed, and there is a dense RSAE spectrum due to the small alpha particle characteristic dimensionless orbits.